Teriparatide – Indications beyond osteoporosis - Cheng, Marilyn Lee (Medknow Publications & Media Pvt Ltd, 2012)
Osteoporosis is a condition of impaired bone strength that results in an increased risk of fracture. The current and most popular pharmacological options for the treatment of osteoporosis include antiresorptive therapy, in particular, oral bisphosphonates (alendronate, risedronate, ibandronate). Anabolic agents like teriparatide have widened our therapeutic options. They act by directly stimulating bone formation and improving bone mass quantity and quality. Two forms of recombinant human parathyroid hormone (PTH) are available : full-length PTH (PTH 1–84; approved in the EU only) and the 1–34 N-terminal active fragment of PTH (teriparatide, US FDA approved). This review aims to discuss the benefits of teriparatide beyond the currently licensed indications like fracture healing, dental stability, osteonecrosis of jaw, hypoparathyroidism, and hypocalcemia.